El colon Ilio-Pélvico en los peruanos II Parte: Relaciones, longitud y dolicosigmoides - Escudero, Francisco (1966)
We have seen the variety of positions that can be found in the sigmoid colon. Some authors attribute this feature to the existence of their free meso , which allows great mobility , because the parietal insertion of meso is shorter than the visceral . At the same time this would cause excessive mobility reduction of amplitude and degree of sclerosis. you can get from the abutment of two roots to the full height of meso because inflamadones and infections neighborhood , propagated via linfótico ( 152 ) for some ; other as a result of sub- occlusive crises iterative state period can determine compressions dolicocolon vessel at the level of twisting. In principle , the gross anatomy teaches that adosamiento fascia fixing portions of the descending colon and colon Ilicco not exist in the sicrnoides , since precisely this mobile part begins at the point where the one ends . However, this process of coalescence is subject , according to the classical authors, numerous variations : being able to reach the inner edge of the iliopsoas or a little higher near the iliac crest , where in the latter case the broader sigmoid loop ; other times 6. ] adosamiento missing on the back , leaving a meso 1 to 2 cms. in the latter portion of the lumbo -iliac colon and in other cases is so irregular , offering only a few inches without abutment , forming the paracolic pits , real funds retrocólicos sac , where foul welding (150) (438).